Pharmacophore-based models for therapeutic drugs against phosphorylated tau in Alzheimer's disease. Issue 2 (February 2019) - Pradeepkiran, Jangampalli Adi; Reddy, Arubala P.; Reddy, P. Hemachandra
Highlights: Tau plays an important part in the formation of axonal microtubules. Phosphorylated tau (P-tau) plays an aberrant part in causing Alzheimer's disease. P-tau is a potential therapeutic target in Alzheimer's disease and tauopathies. P-tau-targeted 3D pharmacophore drug models are important for Alzheimer's disease and tauopathies. Abstract : Phosphorylated tau (P-tau) has received much attention in the field of Alzheimer's disease (AD), as a potential therapeutic target owing to its involvement with synaptic damage and neuronal dysfunction. The continuous failure of amyloid β (Aβ)-targeted therapeutics highlights the urgency to consider alternative therapeutic strategies for AD. The present review describes the latest developments in tau biology and function. It also explains abnormal interactions between P-tau with Aβ and the mitochondrial fission protein Drp1, leading to excessive mitochondrial fragmentation and synaptic damage in AD neurons. This article also addresses 3D pharmacophore-based drug models designed to treat patients with AD and other tauopathies.